Case report: Radiography and computed tomography of tension pneumoperitoneum caused by gastric perforation in a dog - Kim, Myounghun; Jeong, Jeongyun; Cho, Changhyeon; Eom, Kidong; Kim, Jaehwan (Frontiers in Veterinary Science, 2024)
Tension pneumoperitoneum is characterized by excessive accumulation of gas in the peritoneal cavity, which leads to cardiorespiratory distress. We present the case of a 4-year-old female Labrador retriever who presented with a severe abdominal distension and panting. Radiography revealed a large volume of free gas in the peritoneal cavity with decreased serosal detail. After emergency needle decompression, ultrasound-guided aspiration of the peritoneal effusion helped confirm septic peritonitis. Computed tomography revealed a gastric mass measuring approximately 3.7 × 5.0 × 5.5 cm, which was suspected to have caused the gastric perforation. A large volume of free gas was present in the peritoneal cavity, causing compression and centralization of the abdominal organs. A low-attenuating cleft suggestive of perforation site near the gastric mass was also observed. Exploratory laparotomy confirmed gastric perforation of approximately 2.2 cm adjacent to the gastric mass. The patient was finally diagnosed with tension pneumoperitoneum caused by gastric perforation. The mass was resected with a 1-2-cm surgical margin, and imprinting cytology indicated gastric carcinoma. The patient was aggressively treated with fluid, analgesic, antithrombotic, and antibacterial therapy. However, the patient's condition continued to deteriorate, and euthanasia was performed at the owner's request. Our report is the first to describe the multimodal imaging features of a dog with tension pneumoperitoneum secondary to gastric perforation caused by gastric neoplasm.